A novel widespread bacterial structure related to the flagellar type III secretion system - Kaplan,M; Oikonomou,CM; Wood,CR; Chreifi,G; Ghosal,D; Dobro,MJ; Yao,Q; McDowall,A; Briegel,A; Beeby,M; Chang,Y-W; Shaffer,CL; et al. (2021)
Abstract The flagellar type III secretion system (fT3SS) is a suite of membrane-embedded and cytoplasmic proteins responsible for building the bacterial flagellar motility machinery. Homologous proteins form the injectisome machinery bacteria use to deliver effector proteins into eukaryotic cells, and other family members have recently been reported to be involved in the formation of membrane nanotubes. Here we describe a novel, ubiquitous and evolutionarily widespread hat-shaped structure embedded in the inner membrane of bacteria, of yet-unidentified function, that is related to the fT3SS, adding to the already rich repertoire of this family of nanomachines.